2021
DOI: 10.1108/caer-12-2019-0230
|View full text |Cite
|
Sign up to set email alerts
|

The effect of export tax rebates on product quality: evidence from China's agricultural product processing industry

Abstract: PurposeThis study aims to establish the linkage among export tax rebate (ETR), firm innovation and product quality of Chinese agricultural product processing industry (APPI), so that more targeted policy implications can be discussed.Design/methodology/approachUsing highly disaggregated firm-product-destination-level data through 2001 to 2013 of Chinese APPI, this study employs a two-way fixed effects specification to establish the linkage between ETR and product quality, while the mediational model is adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(47 reference statements)
0
3
0
1
Order By: Relevance
“…We take firms' R&D investment intensity as a proxy to reflect their prevention efforts to ensure food safety. A higher R&D investment intensity leads to a higher quality of agricultural products produced (Liang et al, 2021). In addition, it could lower the possibility of a firm's products being rejected for food safety reasons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We take firms' R&D investment intensity as a proxy to reflect their prevention efforts to ensure food safety. A higher R&D investment intensity leads to a higher quality of agricultural products produced (Liang et al, 2021). In addition, it could lower the possibility of a firm's products being rejected for food safety reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we use unique monthly export data for vegetables from China from December 2005 to December 2006. Using monthly data allows us to investigate the short‐term impact of standards that might be masked with annual data (Liang et al, 2021), while using data at the firm‐product level instead of product level allows us to identify heterogeneous firm‐level responses. Previous studies either used monthly data at an aggregate level (such as the product level) or firm‐product data at a lower frequency (such as annual data), but not both (Curzi et al, 2020; Dal Bianco et al, 2016; El‐Enbaby et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ini mencakup ketahanan, keandalan, presisi, kemudahan penggunaan, dan aspek utama lainnya. Product quality terkait dengan sejauh mana produk dapat memenuhi kebutuhan dan harapan pelanggan (Liang et al, 2022). Maintaining kualitas produk yang baik penting untuk tetap menjadi pilihan pelanggan dan menciptakan kepercayaan terhadap merek .…”
Section: Brand Imageunclassified
“…Zhang and Song (2022) found that export tax rebates can achieve both economic and environmental benefits for Chinese firms and have an incentive effect on technological innovation. Liang et al (2022) detected that export tax rebates would significant influence the product quality of China's agricultural product processing industry. Sun and Wu (2023) studied how the export value-added tax rebate impacted exporters' product markups by taking data of China's industrial enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%